Spatial characteristics and health risks assessments of trace metal pollution from road dusts in the industrialized city of Bangladesh - Masum Howlader; Ashik Md Mamun; Mohammad Mahfuzur Rahman; Md Hasibur Rahman; Sadhon Chandra Swarnokar; Mahfuza Sultana; Md Tanvir Rahman; Tusar Kumar Das (Heliyon)
This study aimed to explore the presence of trace metallic pollutants and its associated health hazards in street dust from Gazipur City, one of Bangladesh's heavily industrialized urban centers. Thirty samples of street dust were collected, considering the city's industrial activity and population density. These samples underwent analysis using ICP-MS to detect potential toxic trace metals. Subsequently, the level of pollution and the associated human health risks were evaluated. The mean concentration of Bi (3.56 ± 2.10 mg/kg), Cd (0.71 ± 0.29 mg/kg), Co (4.03 ± 1.09 mg/kg), Cr (29.05 ± 25.44 mg/kg), Cu (17.36 ± 40.56 mg/kg), Ga (134.96 ± 45.39 mg/kg), In (2.25 ± 1.32 mg/kg), Mn (195.13 ± 191.15 mg/kg), Ni (20.31 ± 19.67 mg/kg), Pb (16.28 ± 3.68 mg/kg), Ti (1.72 ± 1.51 mg/kg) and Zn (44.96 ± 22.40 mg/kg). The element-specific environmental indices represent that the geo-accumulation index follows the descending order In (3.55 ± 1.54) > Bi (3.48 ± 1.08) > Ga (2.51 ± 0.48) > Cd (1.06 ± 0.73) > Pb (−0.23 ± 0.33), while the contamination factor fallows the descending order In (22.54 ± 12.57) > Bi (20.96 ± 12.13) > Ga (8.99 ± 2.97) > Cd (3.53 ± 1.41) > Pb (1.30 ± 0.29) > Zn (0.64 ± 0.31). The average calculated pollution load index is 0.68. The results of the dendrogram showed that those toxic trace metallic pollutants mainly originate from two different sources. The results of PCA (principal component analysis) also support the results of the dendrogram, which illustrate that the corrosion and weathering of automobile parts and other metal materials are the main contributors of Cd, Co, Cr, and Pb. In contrast, the use of leaded gasoline, corrosion in car surfaces and road paint are the main contributors of lead in road dust. The hazard index (HI) showed that Cr, Co, and Pb impose moderate to high non-carcinogenic human health risks. The infant's cancer risk for Cd (1.66−05) and Cr (1.59−04) is very close to the upper limit (10−4 to 10−6). Additional protective measures ought to be contemplated to diminish exposure to road dust among adults and infants.